The relevance of the Benedictine, Franciscan, and Taizé Monastic Traditions for retreat within the Dutch Reformed Tradition: An epistemological reflection - Dreyer, Yolanda (University of Pretoria, 2013)
Thesis (PhD (Practical Theology))--University of Pretoria, 2006.